Knowledge, attitude and practices regarding work related hazards among salt workers in Marakkanam, Tamil Nadu - Cherian, Johnson; Singh, Zile; Bazroy, Joy; Purty, Anil J.; Natesan, Murugan (International Journal Of Community Medicine And Public Health, 2019)
Background: The salt pan workers are exposed to severe health hazards like extreme heat, intense manual labour, direct contact with salt, sunlight glare from salt crystals. This paper describes their knowledge, attitude and practices (KAP) regarding their work related hazards as well as availability and use of personal protective equipments (PPEs). Methods: A community based cross sectional study was conducted in 4 randomly selected villages among the 10 salt worker villages in Marakkanam, Tamil Nadu. A house to house survey of the selected villages enrolled 331 salt workers. The data was collected using a pre designed and pre tested questionnaire. Results: Majority of salt worker (78.5%) reported of being aware of one or more hazards like physical stress (70.7%), direct sunlight (38.7%) and glare from salt crystals (16%) in salt work that resulted in musculoskeletal problems, ophthalmic problems, headache and giddiness. 87% of the salt workers were aware of one or the other personal protective equipments. However, only less than 10% were using the conventional PPEs. The reasons for not using PPE were mainly inconvenience in using and PPE not provided by the employer. Conclusions: Most of the study population is aware of the hazards as well as one or the other methods of protective equipment but actual use of PPE is very low because of non-availability and perception of inconvenience in using them. There is a large gap between awareness and practice regarding PPE usage among these salt workers.